Cyber Hygiene Best Practices in Higher Educational Institutes - Shalabh Agarwal; Anweshan Mukherjee (Mathematics and Computer Science: Research Updates Vol. 2, 2025)
In this world where almost everything is shifting to an online mode, cyber hygiene is of utmost importance. The recent pandemic has made us realize the wonders that can be done by shifting to the online mode or at least by transforming some of the work to an online platform thus operating a hybrid platform. The Internet has become one of the integral parts of our daily lives. It has transformed the way we communicate; make friends, share updates, play games, and shop. They are impacting most aspects of our day-to-day life. Education is one of the important sectors for dissemination of information on prevention of cyber-crimes and reiterated that students can act, as a force multiplier to create an ecosystem for cyber security and to prevent cyber-crimes. Cyberspace connects us virtually with crores of online users across the globe. With the increasing use of cyberspace, cybercrimes especially against women and children such as cyberstalking, cyberbullying, cyber harassment, child pornography, rape content, etc. are also increasing rapidly. To stay safe in the online world, it is important to follow some cyber-safe practices which may help in making our online experience more productive. Cyber Hygiene is the need-of-the-hour in the world which is rapidly transforming to an online mode. This paper focuses on how cyber hygiene can be introduced and implemented in higher educational institutes so that both direct and indirect stakeholders of the institute are safe from security threats. The study concluded that building a routine around cyber hygiene will help prevent cybercriminals from causing security breaches or stealing personal information. At the same time, cyber security is a highly dynamic concept, it is essential to continuously upgrade the cyber hygiene policies and practices to keep up with the increasing threats in the digital world.